FORMULASI GEL EKSTRAK BATANG PEPAYA SEBAGAI ANTIBAKTERI TERHADAP BAKTERI STAPHYLOCOCCUS AUREUS - Amalia Eka Putri; Kristina Handayani (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2020)
Infectious disease is an important disease in Indonesia. Infectious diseases can be caused by pathogenic microorganisms such as the bacterium Staphylococcus aureus ATCC 25923. Infectious diseases can be treated with antibiotics, but antibiotics now resistance.Therefore, other alternatives such as are needed papaya stem which can be used as an antibacterial against S.aureus ATCC 25923. The purpose of this study was to determine the antibacterial activity of papaya stem extract gel against Staphylococcus aureus ATCC 25923. Papaya stem sample extracted using a method soxhletation with 96% ethanol. The extract was made into a gel dosage with a concentration of 5%. The positive control used is clindamycin and the negative control is gel without extract. The results of the papaya stem gel antibacterial activity test showed that the papaya stem gel had antibacterial activity against S.aureus ATCC 25923. The papaya stem extract gel preparation with a concentration of 5% had an average inhibition zone diameter of 18,56±0,51mm. The antibacterial activity is thought to come from the flavonoids, tannins, and saponins contained in the papaya stem fraction.